Periodismo digital y responsabilidad social. Contagios VIH en la pospandemia en Ecuador - Herrera Chávez, Janina Lourdes (2023)
This study focuses on media coverage of HIV infections in Ecuador during the post-pandemic period and its relationship with the ethical principles of social responsibility in digital journalism. The HIV/AIDS epidemic, as a global health issue with profound impacts on people's lives, and its coverage in digital media are essential for informing and reducing stigma. Between January and June 2021, the coverage of HIV infections in Ecuadorian digital media was analyzed. The results highlight that this coverage was mainly informative, focused on statistics and epidemiological data, but lacked a contextual and human approach that would highlight the experiences of those affected. Furthermore, ethical principles of social responsibility, such as respecting privacy and dignity, were not always properly applied when disseminating information about HIV. To address these shortcomings, a theoretical application alternative is proposed based on training and raising awareness among journalism staff about the importance of responsible HIV coverage in the post-pandemic context. Four training sessions are proposed to improve the quality of information and promote the application of ethical principles in digital journalism. This study contributes to the understanding of the relationship between digital journalism and social responsibility in the context of HIV in Ecuador. The results and recommendations have the potential to benefit society by promoting greater awareness and understanding of HIV in the post-pandemic period.